1995
DOI: 10.1248/bpb.18.683
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic Constituents from Oolong Tea Stem.

Abstract: The antiallergic constituents of oolong tea stem were examined. The stem extracts inhibited the 48 h homologous passive cutaneous anaphylaxis (PCA) reactions or rats in a dose-dependent manner and showed the same extent of inhibitory activity as ketotifen. All antiallergic constituents from the stem were concentrated into chloroform and ethyl acetate fractions, when extracted by various solvents. These fractions were treated with polyvinylpolypyrrolidone (PVPP), which resulted in the elimination of antiallergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…It has been reported that some polyphenols could exert anti-allergic activities. [5][6][7][8][9][10] It is also known that tomato contains many polyphenols such as caffeic acid and rutin.…”
mentioning
confidence: 99%
“…It has been reported that some polyphenols could exert anti-allergic activities. [5][6][7][8][9][10] It is also known that tomato contains many polyphenols such as caffeic acid and rutin.…”
mentioning
confidence: 99%
“…conversely, omori et al reported that reishi reduced the renal disorder induced by CDDP (25). however, our study only had 3.5 day duration and the longer-term effect of MAK on injury to these organs needs to be established in further studies.…”
Section: Discussionmentioning
confidence: 66%
“…EGCG is known to inhibit immediate hypersensitivity reactions (38,45). We first compared in vivo effects on mast cell-dependent PCA reactions between different tea catechins, EGCG and its Omethylated derivatives (Fig.…”
Section: Effects Of Tea Catechins On Pca Reactionsmentioning
confidence: 99%